MATCH AND MISMATCH BETWEEN LEARNING STYLES OF EFL STUDENTS AND TEACHING STYLES OF EFL TEACHERS - Zahratul Jannah; Veni Roza; Merry Prima Dewi (ELP (Journal of English Language Pedagogy), 2021)
The purposes of this research were to find out what students’ learning styles and teachers’ teaching styles at MTsN 02 Bukittinggi and to find out what are the matches or mismatches between students’ learning styles and teachers’ teaching styles at MTsN 02 Bukittinggi. The design of this research was combining both quantitative and qualitative research. The population of this research was grade VIII at MTsN 02 Bukittinggi. The sample was collected from two classes with a total number of students was 78 students and two different English teachers who taught in both classes. The instrument of this research was questionnaire and interview. The result showed that both classes had the same dominant learning style. In class VIII.6, there were dependent, participant, and collaborative learning styles. Meanwhile, in class VIII.7, the dominant learning styles was collaborative, participant and dependent learning style. While the teachers also had the same dominant teaching styles which were expert, formal authority, and personal model teaching style. Based on the theory of Grasha (2002) about the relationship of learning and teaching style, the researcher found that there was a match between learning styles and teaching styles at MTsN 02 Bukittingg and it was in cluster 2.